Uji Efektivitas Antibakteri Ekstrak Etanol Kulit Pisang Kepok (Musa Acuminata Balbisiana Colla) dan Daun Salam (Syzgiyum Polyanthum) Terhadap Bakteri Escherchia Coli - Hanifa, Noha; Dhanti, Kurnia Ritma; Kurniawan, Kurniawan; Mulyanto, Arif (ORYZA ( JURNAL PENDIDIKAN BIOLOGI ), 2024)
This research aims to examine the effectiveness of the combination of bay leaf extract and kepok banana peel extract as an anti Escherichia coli bacteria. This type of research is experimental with a posttest only control group design with a comparison of kepok banana peel and bay leaves, F1 (25%: 75%), F2 (50%: 50%), F3 (75%: 25%). The research results showed that the most effective extract was F1 treatment (25%:75%) with an inhibitory power of 9.7mm2. The results of the statistical analysis showed that the inhibition test treatment against E. Coli bacteria using different concentrations showed a mean difference in the area of ​​the inhibition zone with a significant value of 0.000 (p<0.05). The results of the Duncan Multiple Range Test (DMRT) showed that K+ (chloramphenicol) was significantly different from the concentrations of F1, F2 and F3. Testing the effectiveness of Kepok banana peel extract and bay leaf extract against E. coli bacteria showed that F1 treatment was effective in preventing bacterial growth against the F1 combination of 25% Kepok banana peel and 75% bay leaves.